Evaluating the Efficacy of Mass Media and Social Marketing Campaigns in Changing Consumer Financial Behavior - Mulaj, Florentina; Jack, William (World Bank, Washington, DC, 2013)
Mass media and social marketing programs are cheap, scalable, and potentially effective means of influencing consumers' financial behavior and decisions. In light of this potential, and in order to provide clear policy direction, this paper provides an overview of the existing and ongoing research efforts in this domain, and highlights the importance of expanding the evidence base by conducting rigorous impact assessments in this field. Exploring four case studies, it provides lessons in designing effective evaluations specifically targeting mass media and social marketing programs on consumer financial management, highlights the value of incorporating insights from behavioral psychology in program design, and suggests avenues for future research.